2021
DOI: 10.1002/vetr.949
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of enflicoxib for treatment of canine osteoarthritis: A 6‐week randomised, controlled, blind, multicentre clinical trial

Abstract: Background: Enflicoxib is a new COX-2 selective NSAID intended for the treatment of pain and inflammation associated with canine osteoarthritis. Methods: A prospective, multisite, blinded, randomised, controlled, parallelgroup field study was performed to determine the efficacy and safety of enflicoxib in canine osteoarthritis. A total of 242 dogs were randomised to receive enflicoxib at 4 or 2 mg/kg, mavacoxib at 2 mg/kg or placebo, orally. Enflicoxib and placebo were administered once weekly from day 0 to da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 49 publications
7
11
0
Order By: Relevance
“…These results confirm the findings of Salichs et al [ 37 ], in which a tendency for a faster onset of action was also observed for enflicoxib following the same treatment schedule. The efficacy obtained in the mavacoxib group was somewhat lower than previously described by Payne-Johnson et al [ 42 ], were mavacoxib treated dogs showed an overall improvement of 93.4% for the owner assessment and similar results for the veterinary assessment.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…These results confirm the findings of Salichs et al [ 37 ], in which a tendency for a faster onset of action was also observed for enflicoxib following the same treatment schedule. The efficacy obtained in the mavacoxib group was somewhat lower than previously described by Payne-Johnson et al [ 42 ], were mavacoxib treated dogs showed an overall improvement of 93.4% for the owner assessment and similar results for the veterinary assessment.…”
Section: Discussionsupporting
confidence: 92%
“…The veterinarians assessed pain and lameness using NRS as described by several authors [ 39 43 ]. This NRS included the assessment of four parameters in the following order: posture while the dog was standing, lameness at walk, lameness at trot and pain at palpation/manipulation of the affected joint as described in Salichs et al [ 37 ]. A factor of two was applied to place more weight on lameness at walk and at trot as part of the clinical picture of OA [ 39 , 40 , 43 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Importantly, the efficacy of such concentrations was demonstrated in clinical studies at the recommended dose and even at half the recommended dose (Salichs et al, 2021 ). It is also worth noting that the pharmacological effect of enflicoxib treatment could be based not only on a direct effect on enzymatic COX‐2 activity but also on COX‐independent immunosuppressant and anti‐inflammatory actions shared by parent and main metabolite.…”
Section: Discussionmentioning
confidence: 99%